Dicamba Impacts on Aquatic Bioindicators and Non-Target Plants - Pereira, Pâmela Castro [UNESP]; Brunetti, Isabella Alves [UNESP]; da Silva, Ana Beatriz; de Oliveira, Ana Carolina [UNESP]; da Cruz, Claudinei; Duke, Stephen Oscar; de Carvalho, Leonardo Bianco [UNESP] (MDPI, 2025)
Use of dicamba, an auxin-mimic herbicide, has increased in recent years. Both the effects of dicamba on non-target plants and the determination of a biological model to determine the dicamba ecotoxicity dynamics are important to monitor the correct and safe use of this herbicide. The objectives of this study were to determine the effects of low doses (simulating herbicide drift) and to determine the acute toxicity of dicamba to aquatic bioindicator species (Lemna minor, Pomacea canaliculate, Hyphessobrycon eques, and Danio rerio) and terrestrial non-target plants (Cucumis sativus, Solanum lycopersicum, and Lactuca sativa) in tropical conditions. Measurements of acute toxicity of dicamba at the concentrations that cause 50% of symptoms of injury (LC50) and other biometric variables were performed. Dicamba was virtually non-toxic to all aquatic bioindicator species (LC50 > 118.0 mg L−1), while it was highly toxic to all terrestrial non-target plants (LC50 < 0.5 mg L−1). Severe injury symptoms (70% to 100%) caused by application of low doses of dicamba were found for all non-target terrestrial plants. Severe injury symptoms (70% to 100%) caused by volatilization of dicamba were found only for S. lycopersicum. Since S. lycopersicum was found as the most sensitive non-target plant, showing high injury symptoms caused by dicamba and significant injury from volatilized dicamba, this species is suitable for environmental monitoring of dicamba applications.